Pengaruh Pemberian Kue Kering Garut dengan Penambahan Serat Larut dan Kayu Manis terhadap Penderita Diabetes Melitus Tipe 2: The Effect of Arrowroot Cookies with the Addition of Soluble Fiber and Cinnamon on Type 2 Diabetes Patients - Atika Anif Prameswari; Lily Arsanti Lestari; I Dewa Putu Pramantara (Amerta Nutrition, 2026)
Background: Type 2 Diabetes Mellitus (T2DM) is a metabolic condition characterized by poor glucose metabolism and chronic hyperglycemia caused by insufficient insulin secretion. Diets high in dietary fiber and resistant starch have been found to improve glycemic control and lower the risk of complications in people with T2DM. A combination of arrowroot tuber (Maranta arundinacea), cinnamon, and porang (Amorphophallus oncophyllus) derived glucomannan has been formulated into a functional snack aimed at individuals with T2DM. This snack is anticipated to contribute to the reduction of blood glucose levels. Objectives: This study investigates the efficacy of arrowroot-based cookies supplemented with cinnamon and porang derived glucomannan in lowering fasting blood glucose (FBG) levels in individuals with type 2 diabetes. Methods: A Randomised Controlled Trial (RCT) design with pre- and post-test evaluations was employed in this investigation. Male and female T2DM patients between the ages of 40 and 60 who had been taking glimepiride and/or metformin for at least three months made up the subjects. The intervention group ate five arrowroot cookies enhanced with porang- derived glucomannan and cinnamon every day for eight weeks. Results: The control group had a mean Fasting Blood Glucose (FBG) level of 149.25±17.25 mg/dL at baseline and dropped to 136.66±12.26 mg/dL after the study period (p-value=0.041), whereas the intervention group had a mean FBG level of 153.66±13.23 mg/dL at baseline and 157.66±19.18 mg/dL after treatment (p-value=0.239). Conclusions: FBG levels among subjects with type 2 diabetes did not significantly decrease after eating arrowroot cookies enhanced with porang glucomannan for eight weeks.